Isospora bocamontensis (Pereira et al., 2011) (Protozoa: Apicomplexa) em cardeais-amarelo Gubernatrix cristata (Vieillot) (Passeriformes: Emberezidae) - Pereira, Larissa Quinto (2011)
The yellow-cardinal (Gubernatrix cristata) is a passerine bird that occurs in southern Brazil, especially along the border with Uruguay and Argentina. It is an endangered bird and your population is decreasing due to loss and fragmentation of your habitats besides illegal capture. In Brazil, its captive breeding is regulated by the government agency and allows the maintenance of individuals in different places with different breeding systems. Among the parasites that affect passerines, the coccidia of the genus Isospora are the most easily found in both captive and free-living birds. Commonly cause injury to the intestinal tissue and could occasionally affect other organs. In this work, we describe a new species of Isospora in yellow-cardinal and also establish the occurrence of the protozoan and its relationship with factors such as sex, use of parasiticide products, type of cage, contact with feces, food type and frequency of cleaning in birds kept in captivity in the city of Santa Maria, Rio Grande do Sul, Brazil.